Empirical Study on the Indicators of Sustainable Performance – the Sustainability Balanced Scorecard, Effect of Strategic Organizational Change - Maria Radu (Amfiteatru Economic Journal, 2012)
The sustainable organizational change has an ever increasing importance, leading to the rethinking of the management and systems of performance measurement and monitoring within the companies. As a reaction to current economic phenomena, in the first section of this work we tried to bring out the need for using the couple Balanced Scorecard - Corporate Social Responsibility by companies. Thus, companies involved in sustainable actions must grant a great importance to the impact of environmental, social and economic factors in providing added value, informing the interested parties and reflecting the reporting of sustainable performance. As a consequence, in the second part of the work we present the Sustainability Balanced Scorecard for the implementation of efficient strategies which cumulate the economic, social and environmental aspects as integrating system for sustainable performance and as a new challenge for organizational change. The key performance indicators included in the Sustainability Balanced Scorecard are quantified by the indicators of sustainable development, based on which the empirical research described in the third section of the work was achieved. Through the quantitative analysis of the economic and ecological indicators (Gross Domestic Product per capita, respective, Environmental Performance Index) in correlation with the social indicator (Global Competitive Index), we conclude that the implementation of green strategies by companies leads to sustainable economic growth.
Keywords: D60; O12; Q56; 330; sustainability; organizational change; Sustainability Balanced Scorecard; performance indicators; competitiveness